Rare variants in MME, encoding metalloprotease neprilysin, are linked to late-onset autosomal-dominant axonal polyneuropathies - Auer-Grumbach, Michaela; Toegel, Stefan; Schabhüttl, Maria; Weinmann, Daniela; Chiari, Catharina; Bennett, David L. H.; Beetz, Christian; Klein, Dennis; Andersen, Peter M.; Böhme, Ilka; Fink-Puches, Regina; Gonzalez, Michael; et al. (The American journal of human genetics, 2016)
Axonal polyneuropathies are a frequent cause of progressive disability in the elderly. Common etiologies comprise diabetes mellitus, paraproteinaemia, and inflammatory disorders, but often the underlying causes remain elusive. Late-onset axonal Charcot-Marie-Tooth neuropathy (CMT2) is an autosomal-dominantly inherited condition that manifests in the second half of life and is genetically largely unexplained. We assumed age-dependent penetrance of mutations in a so far unknown gene causing late-onset CMT2. We screened 51 index case subjects with late-onset CMT2 for mutations by whole-exome (WES) and Sanger sequencing and subsequently queried WES repositories for further case subjects carrying mutations in the identified candidate gene. We studied nerve pathology and tissue levels and function of the abnormal protein in order to explore consequences of the mutations. Altogether, we observed heterozygous rare loss-of-function and missense mutations in MME encoding the metalloprotease neprilysin in 19 index case subjects diagnosed with axonal polyneuropathies or neurodegenerative conditions involving the peripheral nervous system. MME mutations segregated in an autosomal-dominant fashion with age-related incomplete penetrance and some affected individuals were isolated case subjects. We also found that MME mutations resulted in strongly decreased tissue availability of neprilysin and impaired enzymatic activity. Although neprilysin is known to degrade β-amyloid, we observed no increased amyloid deposition or increased incidence of dementia in individuals with MME mutations. Detection of MME mutations is expected to increase the diagnostic yield in late-onset polyneuropathies, and it will be tempting to explore whether substances that can elevate neprilysin activity could be a rational option for treatment.
Gesehen am 16.06.2021